(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
This study investigated the nexus between perceptions of supervisors and supervisees panacea as instructional supervision as a means of enhancing teaching effectiveness in the 21st-century classroom in Bakassi Local Government Area of Cross River State, Nigeria. The study employed a quantitative research approach, descriptive design were used. The population of the study comprised 44 public secondary school teachers. Data were collected through questionnaire from 21 teachers purposively chosen from a population of all public secondary schools in Bakassi. The instrument used for data collection was a 40 item questionnaire titled: Perception of Supervisors and Supervisees on Instructional Supervision Effectiveness Questionnaire (PSSISEQ) and analyzed with SPSS descriptive statistic. The results indicated that the attitudes of the superintendents and principals generally were positive toward instructional supervision. For supervisors, classroom observations and feedback were highlighted, whereas for supervisees collaborative support and professional growth were important. The research findings were that the concept of positive instructional supervision makes a substantial meaningful make in the teachers’ effectiveness and thus, it is recommended that supportive and collaborative supervisory models should be institutionalized in response to the current educational needs.